Community Service Learning with Unemployed Young Nova Scotians - De Schiffart, Clarence (Canadian Journal of Counselling and Psychotherapy, 2007)
Community Service Learning for Unemployed Youth is a learning-by-doing framework in Nova Scotia that uses tools, techniques and processes found within service learning, career development, and community development principles. This framework and the community based programs under this framework, target unemployed youth. The approach actively engages young people in their own learning by giving them the opportunity to perform services that directly benefit their community. By incorporating this framework, community service learning for unemployed youth helps to build life-long connections between youth, their communities and the rapidly changing world of work.